Travel agency management : an introductory text - Chand, Mohinder (New Delhi, India : Anmol Publications, 2007)
Travel Agency Management was contributed in the year 2000 to cater the needs of tourism Students and Industrial professionals. However, from the couple of years, Important academic advances are going on and teaching professional are trying to capture them. Travel Agency Management - An Introductory Text" is meant for the students of travel agency management, tour packaging management, Airline Ticketing, HRD for tourism and hotel management, classes in universities, colleges and tourism and hotel management institutions.
Introduction to travel and tourism -- Organisational structure and functions of travel agency business -- Itinerary development -- Tour packaging management -- Tour costing and pricing -- Introduction to airline ticketing -- Hotel industry-an introduction -- Travel agency marketing -- Travel trade organisations associations -- Human resource development for tourism -- travel agency accounting -- Financing tourism ventures in India -- Public sector tourism enterprises and tour packaging business -- Cruise industry-a changing dimension in tourism.
Keywords: TRAVEL AGENTS